RELIABILITY AND HETEROGENEITY OF REAL ESTATE INDEXES AND THEIR IMPACT ON THE PREDICTABILITY OF RETURNS - Battaglia, Francesca; Porzio, Claudio; Sampagnaro, Gabriele (Journal of Advanced Studies in Finance; Vol 1 No 2 (2010): JASF Volume I Issue 2 Winter 2010, 2010)
This paper addresses the issue of data quality in the real estate market. In many countries, the returns indices for direct markets are provided by several sources differing in terms of the methodology adopted and index weights. These differences produce a lack of informative standardization, which could negatively affect the ability of market participants to make predictions. Focusing on the Italian real estate market, the aim of this paper is therefore twofold: to investigate the reliability of property data sources and to assess the impact for financial intermediaries involved in real estate investing. Our results show a significant level of divergence between the data, and considerable implications for those financial institutions dealing with them. These findings conflict with the requirements of an efficient (or at least sub-efficient) market.